Assessment and management of neonatal pain: a best practice implementation project. Issue 1 (14th March 2023) - Zhou, Xuan; Zhou, Kai; Yang, Ming; Wu, Hongli; Chen, Qiuan; Li, Ting; Zeng, Jiali; Li, Dan; Ou, Yulan; Wu, Yanni
ABSTRACT: Background and aims: Neonates are exposed to varying degrees of pain during their hospitalization, which are going to have a profound impact on their lives. Interventions to alleviate neonatal pain are inadequate and inconsistent. The project aims to promote evidence-based practice (EBP) for the assessment and management of neonatal patients with acute pain and to evaluate the impact of these practices on neonatal pain in hospital. Methods: The current project was conducted in the neonatal department of a tertiary hospital in China. Five audit criteria were developed for baseline and follow-up audits. The project used the JBI PACES software and JBI's Getting Research into Practice audit and feedback tool to take evidence-based healthcare into practice. A total of 100 neonates with acute pain procedures were evaluated at baseline and follow-up audit. Results: The results showed a poor compliance of the five audit indicators in the baseline audit and a significantly improved compliance of the five audit indicators in the follow-up audit. Compared to the baseline audit, audit criterion 1 increased from 0% to 86.1%, audit criterion 2 increased from 36.1% to 82.5%, audit criterion 3 increased from 12% to 61%, audit criterion 4 increased from 0% to 66%, and audit criterion 5 increased from 6% at baseline to 71% in the follow-up audit. Conclusion: The project found that EBP can help nursing staff effectively manage neonatal patients who are experiencing acute painful operations. Further studies are necessary to ensure the sustainability of the criteria in the project.